Elevated monocyte-to-HDL cholesterol ratio predicts post-stroke depression - Li, Yaqiang; Zhang, Mei; Xue, Min; Liu, Dalei; Sun, Jinglong (Frontiers in Psychiatry, 2022)
Objectives: Inflammation plays an important role in the development of depression after stroke. Monocyte-to-HDL Cholesterol Ratio (MHR) recently emerged as a novel comprehensive inflammatory indicator in recent years. This study aimed to investigate whether there is a relationship between MHR levels and post-stroke depression (PSD). Methods: From February 2019 to September 2021, patients with acute ischemic stroke (AIS) were recruited within 7 days post-stroke from the two centers and blood samples were collected after admission. The 17-item Hamilton Depression Scale (HAMD-17) was used to measure depressive symptoms at 3 months after stroke. Parents were given the DSM-V criteria for diagnosis of PSD. Results: Of the 411 enrolled patients, 92 (22.38%) patients were developed with PSD at 3-months follow-up. The results also showed significantly higher level of MRH in patients with depression (0.81 (IQR 0.67-0.87) vs.0.61 (IQR 0.44-0.82), P＜0.001) at admission than patients without depression. After adjustment for potential confounding factors, the odds ratio of PSD was 5.018 (95% CI: 1.694-14.867) for the highest tertile of MHR compared with the lowest tertile. Based on the ROC curve, the optimal cut-off value of MHR as an indicator for prediction of PSD was projected to be 0.55, which yielded a sensitivity of 87% and a specificity of 68.3%, with the area under the curve at 0.660 (95% CI: 0.683-0.781; P=0.003). Conclusions: Elevated level of MHR was associated with PSD at 3 months, suggesting that MHR might be a useful Inflammatory markers for PSD.